Feminist epistemology after postmodernism: Critiquing science, technology and globalisation - Braidotti, Rosi (Interdisciplinary Science Reviews, 2007)
This article provides a reasoned overview of contemporary developments within feminist theories of the subject after the decline of postmodernist thought. It stresses the foundational importance of feminist situated epistemology, and hence of a brand of materialism that stresses embodiment and embedded perspectives. The article explores neo-materialist feminist theories in a number of areas, with special emphasis on science and technology studies and critiques of globalisation. It argues that the neo-materialist trend results in a new call for an ethics attuned to the complexity of our era.
Keywords: approches et analyses; bio-technologie; discipline; environnement; féminisme matérialiste; philosophie; postmodernisme; projet charge mentale; ressource en ligne; sciences humaines; thématiques; épistémologie

Feminism and the body - Schiebinger, Londa (Oxford readings in feminism, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme

The good-natured feminist: Ecofeminism and the quest for democracy - Sandilands, Catriona (University of Minnesota Press, 1999)
The Good-Natured Feminist inaugure une conversation soutenue entre l'écoféminisme et les écrits récents du postmodernisme féministe et de la démocratie radicale. Partant de l'hypothèse que l'écoféminisme est un corpus de théorie démocratique, le livre raconte comment le mouvement est né des débats sur la « nature » ​​dans les féminismes radicaux nord-américains, comment il s'est ensuite mêlé à la politique identitaire et comment il cherche maintenant à inclure la nature dans la conversation démocratique et, surtout, de politiser les relations entre genre et nature dans les milieux tant théoriques qu'activistes.
Keywords: amériques; approches et analyses; cours; environnement; fem3600; genre; identités LGBTQIA2+; militance; postmodernisme; premier cycle; ressource en ligne; régions géographiques; thématiques; écoféminisme; états-unis

Feminism and ecological communities: an ethic of flourishing - Cuomo, Chris J. (Routledge, 1998)
Feminism and Ecological Communities presents a bold and passionate rethinking of the ecofeminist movement. It is one of the first books to acknowledge the importance of postmodern feminist arguments against ecofeminism whilst persuasively preseenting a strong new case for econolocal feminism. Chris J.Cuomo first traces the emergence of ecofeminism from the ecological and feminist movements before clearly discussing the weaknesses of some ecofeminist positions. Exploring the dualisms of nature/culture and masculing/feminine that are the bulwark of many contemporary ecofeminist positions and questioning traditional traditional feminist analyses of gender and caring, Feminism and Ecological Communities asks whether women are essentially closer to nature than men and how we ought to link the oppression of women, people of colour, and other subjugated groups to the degradation of nature. Chris J.Cuomo addresses these key issues by drawing on recent work in feminist ethics as well as teh work of diverse figures such as Aristotle, John Dewey, Donna Haraway adn Maria Lugones. A fascinating feature of the book is the use of the metaphor of the cyborg to highlight the fluidity of the nature/culture distinction and how this can enrich econfeminist ethics and politics. An outstanding new argument for an ecological feminism that links both theory and practice, Feminism and Ecological Communities bravely redraws the ecofeminist map. It will be essential reading for all those interested in gender studies, environmental studies and philosophy.
Keywords: approches et analyses; com5170; cours; discipline; environnement; philosophie; postmodernisme; premier cycle; sciences humaines; thématiques; écoféminisme